Sistemas de gestión integrado oshas 18001:2007 e iso 14001:2004 aplicado a empresas contratistas en Consorcio Minero Horizonte s.a. - Díaz Torres, Wilmar Benjamín (2017)
In the last years a good part of the activity has been realized with the support of contracting enterprises. Although the Law indicates that the workers of a contractor can not be assigned for the principal activity of the contractor, this norm is frequently vulnerable and manipulated to the favor of the Mining Enterprise. Showing the grade of the in – protectiveness of the worker who works for a contracting enterprise; the frequent accidents at work – according to the statistics published by the Ministry of Energy and Mining there have been 899 fatal accidents in the last sixteen years (2000 - 2015) of which 580 of worker working by contractor, that means that 64% of these occurrences have happened to worker who have no working relationship whatsoever with the Mining Enterprises. This indicates that the Administrator of Safety, Occupational Health and environment of the mining enterprises are not sufficient or do not concord whit the reality of the necessity of its strategic partners. Defined the scope of the system, and then make the IPERC of all activities and implement controls at the critical activities and according to our requirements define significant hazards and our objectives, goals and programs to assess compliance. For the implementation phase was developed which indicates procedures step by step how to allocate resources, functions, responsibilities, training programs, participation and consultation; documents control, operational control, emergency preparedness and response. All Companies Contractors at national level should implement a System Safety, Health and Environment either own or adapted. As this will give them guidelines, tools and controls to perform successful management. Then to apply and successfully develop this system Occupational Safety and Health trend of accidents rates.